Effects of community-based antiretroviral therapy initiation models on HIV treatment outcomes: A systematic review and meta-analysis. - Ingrid Eshun-Wilson; Ajibola A Awotiwon; Ashley Germann; Sophia A Amankwaa; Nathan Ford; Sheree Schwartz; Stefan Baral; Elvin H Geng (PLoS Medicine)
Background Antiretroviral therapy (ART) initiation in the community and outside of a traditional health facility has the potential to improve linkage to ART, decongest health facilities, and minimize structural barriers to attending HIV services among people living with HIV (PLWH). We conducted a systematic review and meta-analysis to determine the effect of offering ART initiation in the community on HIV treatment outcomes. Methods and findings We searched databases between 1 January 2013 and 22 February 2021 to identify randomized controlled trials (RCTs) and observational studies that compared offering ART initiation in a community setting to offering ART initiation in a traditional health facility or alternative community setting. We assessed risk of bias, reporting of implementation outcomes, and real-world relevance and used Mantel-Haenszel methods to generate pooled risk ratios (RRs) and risk differences (RDs) with 95% confidence intervals. We evaluated heterogeneity qualitatively and quantitatively and used GRADE to evaluate overall evidence certainty. Searches yielded 4,035 records, resulting in 8 included studies-4 RCTs and 4 observational studies-conducted in Lesotho, South Africa, Nigeria, Uganda, Malawi, Tanzania, and Haiti-a total of 11,196 PLWH. Five studies were conducted in general HIV populations, 2 in key populations, and 1 in adolescents. Community ART initiation strategies included community-based HIV testing coupled with ART initiation at home or at community venues; 5 studies maintained ART refills in the community, and 4 provided refills at the health facility. All studies were pragmatic, but in most cases provided additional resources. Few studies reported on implementation outcomes. All studies showed higher ART uptake in community initiation arms compared to facility initiation and refill arms (standard of care) (RR 1.73, 95% CI 1.22 to 2.45; RD 30%, 95% CI 10% to 50%; 5 studies). Retention (RR 1.43, 95% CI 1.32 to 1.54; RD 19%, 95% CI 11% to 28%; 4 studies) and viral suppression (RR 1.31, 95% CI 1.15 to 1.49; RD 15%, 95% CI 10% to 21%; 3 studies) at 12 months were also higher in the community-based ART initiation arms. Improved uptake, retention, and viral suppression with community ART initiation were seen across population subgroups-including men, adolescents, and key populations. One study reported no difference in retention and viral suppression at 2 years. There were limited data on adherence and mortality. Social harms and adverse events appeared to be minimal and similar between community ART initiation and standard of care. One study compared ART refill strategies following community ART initiation (community versus facility refills) and found no difference in viral suppression (RD -7%, 95% CI -19% to 6%) or retention at 12 months (RD -12%, 95% CI -23% to 0.3%). This systematic review was limited by few studies for inclusion, poor-quality observational data, and short-term outcomes. Conclusions Based on data from a limited set of studies, community ART initiation appears to result in higher ART uptake, retention, and viral suppression at 1 year compared to facility-based ART initiation. Implementation on a wider scale necessitates broader exploration of costs, logistics, and acceptability by providers and PLWH to ensure that these effects are reproducible when delivered at scale, in different contexts, and over time.